Assessment of Clinical Ethics Application and Patient Satisfaction in Anesthesiology Services: A Cross-Sectional Study - Forensa, Habibie Arzt; Suryadi, Taufik; Kulsum, Kulsum (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2026)
Background: Clinical ethics is currently widely discussed in anesthesiology practice in hospitals. The implementation of clinical ethics is very important in providing patient care. Anesthesiology services are a type of medical service that is full of ethical dimensions because each procedure, from pre-operative, perioperative, and post-operative, is directly correlated with the four quadrants of clinical ethics. There have been few studies conducted regarding the implementation of clinical ethics and the quality of patient satisfaction.Objective: The purpose of this study was to describe the implementation of clinical ethics in anesthesiology and the quality of patient satisfaction.Methods: An observational study using cross sectional design was conducted at Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia, in October-December 2023 on 111 patients receiving anesthesiology services, male and female, aged 2-65 years, who will undergo elective surgery.Result: The present study found that the implementation of clinical ethics in anesthesiology services was 62.45%, with each category being medical indications (72.26%), patient preferences (66.21%), quality of life (60.21%), and contextual features (51.12%). Meanwhile, the level of patient satisfaction with anesthesiology services was as follows: strongly satisfied (69.37%), satisfied (18.02%), neutral (8.10%), not satisfied (2.71%), and strongly not satisfied (1.80%). Factors influencing the lack of implementation of clinical ethics in anesthesiology services include short consultation times, inadequate patient understanding of clinical ethics issues, and excessively detailed information. One way to improve the implementation of clinical ethics is by providing comprehensive clinical ethics information during anesthesia consultations and pre-operative care.Conclusion: The implementation of clinical ethics in anesthesiology services was moderate. Higher perceived clinical ethics practices may be associated with increased patient satisfaction; however, causal conclusions cannot be drawn from this study.